The Taliban's virtual emirate: the culture and psychology of an online militant community - Aggarwal, Neil Krishan (Columbia University Press, 2016)
1. Channels of communication in the virtual emirate -- 2. Mullah Omar's leadership in the virtual emirate -- 3. Identity in the virtual emirate -- 4. Jihad in the virtual emirate -- 5. International relations in the virtual emirate -- Epilogue